.Willgerodt Kindler Reaction’s Microwave-Enhanced Synthesis of Thiobenzamides Derivatives in Heterogeneous Acid Catalysis with Montmorillonite K-10 - GBAGUIDI, A. (My University, 2017)
The Willgerodt-Kindler (WK) reaction of is one of most synthesis methods used to access the thioamides. The known to thioamides have made this reaction more attractive in catalytic synthesis methods. Heterogeneous catalysis acid with the montmorillonite K-10 applied to this reaction under activation microwave for the synthesis of phenyl (morpholino) methanethiones derivatives shows that the mixture (aldehyde, sulfur, morpholine and K-10) is not only appropriate, but optimizes the reaction. This solid catalyst was easily separated from the reaction mixture and was recycled at least twice (02) without any loss of activity. Operational simplicity, short reaction times, excellent yields and benign environmental conditions are other advantages of this protocol, thus respecting the principles of green chemistry. Among the thioamides synthesized, 4-(morpholine-4-carbonothioyl)benzoic acid (h) is a novel molecule which to our knowledge has never before been synthesized. We obtained it with a yield of 68%. In summary, we can be concluded that the heterogeneous catalysis acid conditions with the montmorillonite K - 10 favourable to the Willgerodt-Kindler reaction for carbonyl compounds. The structures of thioamides synthesized were characterized and confirmed by highresolution mass spectrometry (HRMS) and nuclear magnetic resonance (NMR) 1D and 2D (COSY, HSQC, HMBC).